2022
DOI: 10.1080/10408398.2022.2053658
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fiber-fortified food consumption on anthropometric measurements and cardiometabolic outcomes: A systematic review, meta-analyses, and meta-regressions of randomized controlled trials

Abstract: Search string details (For EMBASE)('dietary fiber'/exp OR 'alimentary fiber':ti,ab OR 'diet fiber':ti,ab OR 'dietary fiber':ti,ab OR 'dietary fibre':ti,ab OR 'inulin'/de OR 'inuline':ti,ab OR 'pectin'/exp OR 'ispagula'/exp OR 'ispaghul':ti,ab OR 'ispaghula':ti,ab OR 'ispaghula husk':ti,ab OR 'ispagula':ti,ab OR 'isphagula':ti,ab OR 'plantago ovata extract':ti,ab OR 'plantago ovata seed ':ti,ab OR 'plantago seed':ti,ab OR 'plantago seed oil':ti,ab OR 'psyllium':ti,ab OR 'psyllium gum':ti,ab OR 'psyllium hemice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 99 publications
1
7
0
Order By: Relevance
“…Regarding the effect of dietary fiber intake on serum lipid profiles, most of our results concurred with the report from a recent meta-analysis, which showed that fiber-fortified food consumption could significantly reduce the levels of serum TC, TG, and LDL-C, while no significant effect was observed in serum HDL-C concentration (92). However, in contrast, we only found a significant decrease in the subgroup analysis based on β-glucan intervention in the serum TG level, but not in overall pooled ESs.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the effect of dietary fiber intake on serum lipid profiles, most of our results concurred with the report from a recent meta-analysis, which showed that fiber-fortified food consumption could significantly reduce the levels of serum TC, TG, and LDL-C, while no significant effect was observed in serum HDL-C concentration (92). However, in contrast, we only found a significant decrease in the subgroup analysis based on β-glucan intervention in the serum TG level, but not in overall pooled ESs.…”
Section: Discussionsupporting
confidence: 91%
“…These cardiometabolic and anthropometric improvements are attributed to the physicochemical properties of dietary fiber even at intervention dosages less than 15 g day −1 but may require a longer intervention duration for a more pronounced effect. [25] Okara intervention effectively increased total and insoluble fiber intake to the desirable range of 25-30 g day −1 , [26] with RO significantly increasing soluble fiber intake. Dietary fiber undergoes anaerobic fermentation in the gut, generating gaseous intermediates such as hydrogen gas by Bacteroides and Clostridium or carbon dioxide by some Clostridia, although some probiotics can assist with gas removal through re-utilization.…”
Section: Discussionmentioning
confidence: 99%
“…23 Previous systematic reviews have reported the diverse effects of various prebiotics on the composition of the gut microbiota. [24][25][26] A previous study reported that inulin intake selectively increases the abundance of Bifidobacterium in the gut. 27 However, previous studies have not considered the abundance of A. muciniphila.…”
Section: Introductionmentioning
confidence: 99%